2021
DOI: 10.3390/v13040577
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Capacity to Detect Clusters of Rapid HIV Transmission in Varied Populations—United States

Abstract: Molecular cluster detection analyzes HIV sequences to identify rapid HIV transmission and inform public health responses. We describe changes in the capability to detect molecular clusters and in geographic variation in transmission dynamics. We examined the reporting completeness of HIV-1 polymerase sequences in quarterly National HIV Surveillance System datasets from December 2015 to December 2019. Priority clusters were identified quarterly. To understand populations recently affected by rapid transmission,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…54 Response efforts should be scaled to the size and characteristics of the cluster or outbreak and the needs of the transmission network. Although large outbreak responses are often highly visible, 55 CDR also includes intervening in the many clusters detected while still small, 13 which can most effectively limit transmission. 17,23 Therefore, CDR spans routine, day-today efforts to identify and prioritize clusters; initial response to small clusters; and expanded or escalated response to more concerning clusters and outbreaks (Figure 1).…”
Section: Why Is Responding To Clusters and Outbreaks Important?mentioning
confidence: 99%
See 3 more Smart Citations
“…54 Response efforts should be scaled to the size and characteristics of the cluster or outbreak and the needs of the transmission network. Although large outbreak responses are often highly visible, 55 CDR also includes intervening in the many clusters detected while still small, 13 which can most effectively limit transmission. 17,23 Therefore, CDR spans routine, day-today efforts to identify and prioritize clusters; initial response to small clusters; and expanded or escalated response to more concerning clusters and outbreaks (Figure 1).…”
Section: Why Is Responding To Clusters and Outbreaks Important?mentioning
confidence: 99%
“…Analysis by race/ethnicity and transmission category shows that groups experiencing rapid transmission do not necessarily mirror those with higher numbers of diagnoses and that these groups change over time and show substantial geographic variation. 13 Therefore, ongoing, routine analysis by HDs is necessary to identify the networks experiencing rapid transmission. By identifying these networks that are not being effectively reached by existing HIV prevention services, such ongoing analysis presents a vital opportunity to address health equity.…”
Section: What Populations Are Affected By Clusters and Outbreaks?mentioning
confidence: 99%
See 2 more Smart Citations
“…Cluster sizes and transmission rates were significantly higher for PWID than MSM, emphasizing the importance of targeted interventions to avert large outbreaks related to drug use. Notably, Oster et al showed that epidemics among PWID in the US states are also on the rise, comprising 1% and 11% of clustered infections in 2015-2016 and 2018-2019, respectively [7].…”
mentioning
confidence: 99%